On the connection between certain inequalities of the Kolmogorov type for periodic and nonperiodic functions - Babenko, V. F.; Selivanova, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain nonperiodic analogs of the known inequalities that estimateL p -norms of intermediate derivatives of a periodic function in terms of itsL ∞-norms and higher derivative.